Penerapan Program Pendidikan Untuk Anak Berkebutuhan Khusus Tunanetra - Juliatuti, Audri Aisa; Fachrozi, Ahmad Deka; Oktarina, Yeni (PPSDP Undergraduate Journal of Educational Sciences, 2025)
Children with special needs (ABK) are children who have different needs from other children due to certain physical, mental, emotional or social conditions. Education for children with special needs, especially the visually impaired, requires a specialized approach to ensure an inclusive and meaningful learning experience. This study aims to find out about the scope of education for children with special needs who are blind. The method used in this literature review is Systematic Literature Review (SLR), which is a structured and planned review process that aims to answer research questions in a systematic and explicit way, with the main objective being to identify, select and critically evaluate previous research results on education for children with visual impairments. The education of visually impaired children requires a holistic and child-centered approach, with support from the family, environment and community. Proper implementation of inclusive education, the use of adaptive technology and skilled teacher training are essential to improve the learning, participation and social integration of visually impaired children. This research shows that with the right support, visually impaired children can reach their full potential in education and everyday life.